Perjalanan panjang pendidikan luar sekolah di indonesia: analisis sejarah dan relevansinya masa kini - Lahitania, Zahra (Maliki Interdisciplinary Journal, 2025)
Non-formal education in Indonesia has undergone a long historical journey, shaped by the nation’s social, political, and cultural dynamics. Since the colonial era, non-formal education has served as an alternative learning pathway outside the formal system, contributing to community empowerment. Its development has experienced significant transformations during the independence period, the New Order, and the Reform era, focusing on skills improvement, literacy, and character building. This study aims to analyze the historical development of non-formal education in Indonesia and examine its relevance in the present context. The findings indicate that non-formal education plays an essential role in supporting lifelong learning, eradicating illiteracy, and empowering communities. Its relevance remains significant in the modern era, particularly in addressing the challenges of globalization, technological advancement, and the demand for flexible learning opportunities.